Rubber plantation: soil management & nutritional requirement - Daud, Wan Noordin (Universiti Putra Malaysia Press, 2013)
Rubber has been grown commercially in Malaysia since 1903, when the first rubber estate was established in Melaka. Since then, several usage of rubber have been discovered from time to time. Suitable planting area has decreased and to overcome this problem planting of rubber gets into marginal and problem soils. This books describing soil genesis, management and nutritional requirement of rubber on these marginal soils are scarce. This book is written in 10 chapters, covering various aspects of soil management and nutritional requirement with latest information on current technology available in the rubber industry. These include soil series identification, and fertilizer recommendations for sustainable rubber plantation.